Approach or avoidance: Neural correlates of intelligence evaluation from faces. (28th June 2018) - Akimoto, Yoritaka; Yamazaki, Ryuichi; Sugiura, Motoaki; Nouchi, Rui; Terao, Chiaki; Tsukiura, Takashi; Kawashima, Ryuta
Abstract: Intelligence is among the key determinants of power and social status in modern societies. In this functional magnetic resonance imaging study, we examined the neural correlates of intelligence evaluation from faces. Participants underwent scans while they evaluated the perceived intelligence and friendliness of faces. We found that medial orbitofrontal cortex activity increased linearly with friendliness ratings. The relationship between perceived intelligence and brain activity was positively linear in the right caudate nucleus and U‐shaped (i.e., strong responses to unintelligent‐looking or intelligent‐looking faces) in the right anterior insula/inferior frontal gyrus. Perceived intelligence was also significantly positively correlated with both friendliness and attractiveness. Furthermore, intelligence rating scores had a positive linear effect on reaction times in the friendliness rating task, suggesting that participants had greater conflicts when making friendliness judgments for faces that appeared to belong to intelligent individuals. In addition, the degree of this effect predicted individual differences in the positive linear modulatory effect of intelligence scores in the right caudate nucleus. Our interpretation was that the activity in the caudate nucleus revealed an approach‐avoidance conflict with regard to highly intelligent people, that is, they were perceived as attractive but also potentially threatening. Although our interpretations are merely suggestive because we did not measure the approach‐avoidance behaviors directly, our findings have important implications for understanding the dynamics of human interaction in modern societies that increasingly allocate power and status based on intelligence. Abstract : Intelligent‐looking faces induce activation of the right caudate nucleus and positive quadratic responses in the right insula/inferior frontal gyrus. Intelligent‐looking faces also elicit slower reaction times in the friendliness rating task, and the degree of this effect predicts the activation of the right caudate nucleus. These results suggest that people have an approach‐avoidance conflict with regard to highly intelligent people, possibly due to their power in modern societies.